PERSEPSI MASYARAKAT TENTANG PENERAPAN TILANG ELEKTRONIK (Studi Dalam Wilayah Kota Makassar) - Afrisa Cutrima Ayu Hartina; Lukman Ilham; Firman Muin (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract: This article describes the Public Perceptions of the Application of Electronic Traffic (A Study in the Makassar City Area). Data collection techniques by conducting observations, interviews, and documentation. The data obtained from this study, then processed using qualitative analysis to determine the effect of community perceptions and factors inhibiting the application of e-ticketing in Makassar City. The research target is Makassar City community as road users. The results showed that; 1) Public perception of the application of electronic tickets in Makassar City has not yet fully agreed. Some people think that electronic tickets are only a discourse of the government. 2) There are several inhibiting factors for the application of electronic tickets in Makassar City; a) Inadequate road sections, b) lack of supervision from the police officer, c) vehicle density, d) working hours for officers in charge of monitoring CCTV, e) lack of government socialization and the Makassar City police, f) procedures for resolving violations that long and not understood by the people of Makassar City. 3) efforts that must be made by the government in overcoming obstacles that occur in the application of electronic tickets in Makassar City, namely; a) increasing the number of CCTV installations in Makassar City, b) inserting illegal vehicles, c) expanding socialization about electronic tickets, 4) reducing the cost of changing the name of the vehicle, and others.